Historiography and Sources of Problem of Foundation and Functioning of Collegium of Pavlo Galagan (1871–1920) - Oksana Shevchuk (Pedagogical Discourse, 2013)
The article presents systematic and comprehensive analysis basis on the organization and content of education and educationag process at Pavlo Galagan Collegium (1871–1920yy.), which is based on the archival, not popular and published sources. The author describes the main questions, which deals with the analysis of original sources and  historic-pedagogical literature. Analyses and systematization of the resurches are developed in the article. Some new historical facts, not popular and unknown documents, which will extend history of pedagogy knowledge about existence in school practice of Ukraine such unique phenomenon as Pavlo Galagan Collegium. The collegium’s staff kept the best traditions and wanted to reorganize educational process according to present time.